2006
DOI: 10.1097/00004836-200603000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Protracted Hiccups due to Severe Erosive Esophagitis

Abstract: Hiccups are an atypical manifestation and may represent a more severe course of gastroesophageal reflux disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 10 publications
0
15
0
2
Order By: Relevance
“…In addition, etiologies of underlying disorders should be evaluated and corresponding treatment should follow [3]. Non-pharmacological therapy is method to inhibit afferent pathway of vagus nerve, for example, holding a breath, drinking cold water, and inserting a nasogastric tube.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, etiologies of underlying disorders should be evaluated and corresponding treatment should follow [3]. Non-pharmacological therapy is method to inhibit afferent pathway of vagus nerve, for example, holding a breath, drinking cold water, and inserting a nasogastric tube.…”
Section: Discussionmentioning
confidence: 99%
“…If they last longer than 1 month, the condition is classified as "intractable hiccups" [2]. Both pharmacological and non-pharmacological treatment can be used to cure the disease, and if these two methods are ineffective, a nerve block can be considered [3]. We, as the authors in this study, applied a phrenic nerve block after the patient did not respond well to a pharmacological treatment.…”
mentioning
confidence: 99%
“…Even it may be underestimated among the GERD patients, a case series indicated that 7.9% male and 10% female ( P < 0.05) GERD patients had hiccup episodes 32. In addition, acid infusion as a provocative test did confirm the GERD related hiccup, while some prolonged hiccups also responded well to the proton pump inhibitors 33,34. Since severe belching may sometime precede the hiccup episode, perhaps belching is the mechanism leading to hiccup among the GERD subjects 35.…”
Section: Etiology Of Persistent and Intractable Hiccupsmentioning
confidence: 99%
“…It has also been postulated that hiccups can worsen GERD by increasing gastric pressure secondary to diaphragmatic contractions or by negative esophageal pressure with decreased lower esophageal sphincter (LES) tone during the hiccups. 4 The most likely cause of persistent hiccups in our patient is erosive esophagitis. Persistent hiccups have also been reported as the initial presentation of esophageal carcinoma making EGD evaluation and esophageal biopsy critical in these patients.…”
Section: Discussionmentioning
confidence: 65%